IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI MASA ADAPTASI KEBIASAAN BARU (AKB) - Muhamad Tisna Nugraha; Yayat Hidayatulloh; Uus Ruswandi; Mohamad Erihadiana (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
The abstract is to be in the fully-justified text after Indonesia. Abstract with single column as it is here. The abstract is to be in 12-point Times New Roman, single-spaced type, and between 150-200 words in length. Leave two blank lines after the abstract or list three to five keywords related to the articles, then continued with the main text of the article. This study aims to provide a general description of the implementation of multicultural education during the New Habit Adaptation. This as an impact on Coronavirus Diseases 2019 (Covid-19) pandemic and the implementation of social distancing and physical distancing policies to minimize the spread of the outbreak. The method in this study is used a qualitative method with a research design is library research. Meanwhile, the research instruments used in this research are documentation and observation. Based on the results of the research, it shows the implementation of multicultural education in New Habit Adaptation, is to insert the values ​​of multicultural education in the core competencies of learning both online, through applications such as WhatsApp groups, zoom, and google classrooms, and through offline such as by using student handbooks, Student Worksheets, and others. The forms of program activities that can be carried out in implementing multicultural education include a) (content-oriented programs, b) student-oriented programs, and c) socially-oriented programs.